Pengaruh Indeks Pembangunan Manusia (IPM), Pengangguran, Jumlah Penduduk Terhadap Kemiskinan Di Provinsi Jawa Tengah Dengan Zakat Sebagai Variabel Moderasi Tahun 2018-2023 - Laelani, Dian Putri; Nurhadi, Bayu (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to analyze the influence of the Human Development Index (HDI), unemployment rate, and population size on poverty in Central Java Province during the 2018-2023 period, as well as evaluate the role of zakat as a moderating variable. Secondary data were obtained from BPS and BAZNAS of Central Java Province and analyzed using panel data regression and Moderated Regression Analysis (MRA) with E-Views 12 software. The results show that HDI has a significant negative effect on poverty, while unemployment and population size have significant positive effects. Zakat is proven to moderate the relationship between HDI and unemployment on poverty but is not significant in moderating the influence of population size. This study emphasizes the importance of more effective and integrated zakat management to support improvements in HDI, reduce unemployment, and achieve equitable welfare to alleviate poverty in Central Java.